Cytotoxic effects of oosporein isolated from endophytic fungus Cochliobolus kusanoi - Ramesha, Alurappa; Venkataramana, M.; Nirmaladevi, Dhamodaran; Gupta, Vijai K.; Chandranayaka, S.; Srinivas, Chowdappa (Frontiers in Microbiology, 2015)
In the present study, oosporein, a fungal toxic secondary metabolite known to be a toxic agent causing chronic disorders in animals, was isolated from fungus Cochliobolus kusanoi of Nerium oleander L. Toxic effects of oosporein and the possible mechanisms of cytotoxicity as well as the role of oxidative stress in cytotoxicity to MDCK kidney cells and RAW 264.7 splene cells were evaluated in-vitro. Also to know the possible in-vivo toxic effects of oosporein on kidney and spleen, Balb/C mouse were treated with different concentrations of oosporein ranging from 20 uM to 200 µM). After 24 hrs of post exposure histopathological observations were made to know the effects of oosporein on target organs. Oosporein induced elevated levels of ROS generation and high levels of MDA, loss of mitochondrial membrane potential (MMP), induced glutathione hydroxylase production was observed in a dose depended manner. Effects oosporein on chromosomal DNA damage was assessed by Comet assay, and increase in DNA damage were observed in both the studied cell lines by increasing the oosprin concentration. Further, oosporein treatment to studied cell lines indicated significant suppression of oxidative stress related gene (SOD1 and CAT) expression, and increased levels of mRNA expression in apoptosis or oxidative stress